Analysis Of Some Trace Metals In Tin Ore - Yasin, Md. Jazam Md. (Universiti Sains Malaysia, 1982)
Analysis, both qualitative and quantitative, was carried out for some trace metals in a tin ore commercially available as “Amang Feed”